2015
DOI: 10.1002/2014jd022821
|View full text |Cite
|
Sign up to set email alerts
|

On infrasound generated by wind farms and its propagation in low‐altitude tropospheric waveguides

Abstract: Infrasound from a 60‐turbine wind farm was found to propagate to distances up to 90 km under nighttime atmospheric conditions. Four infrasound sensor arrays were deployed in central New Mexico in February 2014; three of these arrays captured infrasound from a large wind farm. The arrays were in a linear configuration oriented southeast with 13, 54, 90, and 126 km radial distances and azimuths of 166°, 119°, 113°, and 111° from the 60 1.6 MW turbine Red Mesa Wind Farm, Laguna Pueblo, New Mexico, USA. Peaks at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…Wind turbines were visible from the launch facility, and others were located along the balloon's flight path. They are a known generator of narrowband infrasound [ Marcillo et al , ]. Aircraft can produce a variety of acoustic signals [ Hubbard , ] and are commonly detected by ground infrasound arrays [ Campus and Christie , ].…”
Section: Discussionmentioning
confidence: 99%
“…Wind turbines were visible from the launch facility, and others were located along the balloon's flight path. They are a known generator of narrowband infrasound [ Marcillo et al , ]. Aircraft can produce a variety of acoustic signals [ Hubbard , ] and are commonly detected by ground infrasound arrays [ Campus and Christie , ].…”
Section: Discussionmentioning
confidence: 99%
“…Under such conditions, therefore, LF and IS levels decay more slowly with distance when compared with higher frequencies. Consistent with this, propagation of sound at the BPF from a 60-turbine wind farm has been recently measured using particularly sensitive equipment as far as 90 km from the source ( Marcillo et al., 2015 ).…”
Section: Wtn Lf and Ismentioning
confidence: 70%
“…Studies of the generation and propagation of IS/LF sound by wind turbines demonstrate that the acoustical energy per unit frequency at the blade-passing frequency (BPF) and at its harmonic frequencies below 10-15 Hz is greater than at higher frequencies. Propagation models and field studies have indicated that sound at these IS/LF frequencies can propagate with less attenuation with distance than higher frequencies because of their lower sound absorption during passage through the air and on reflection from the ground [12,[22][23][24][25][26][27][28]. Added to this is uncertainty regarding the effectiveness of sound insulation of houses at infrasound and low frequencies [29].…”
Section: Possible Perceptual and Physiological Effects Of Wind Turbinmentioning
confidence: 99%